(×-5)(×+2)-1=0 Por favor mim ajudem e pra amanhã
Soluções para a tarefa
Respondido por
1
Boa tarde Viih
(x - 5)*(x + 2) - 1 = 0
x² + 2x - 5x - 10 - 1 = 0
x² - 3x - 11 = 0
delta
d² = 9 + 44 = 53
d = √53
x1 = (3 + √53)/2
x2 = (3 - √53)/2
-
(x - 5)*(x + 2) - 1 = 0
x² + 2x - 5x - 10 - 1 = 0
x² - 3x - 11 = 0
delta
d² = 9 + 44 = 53
d = √53
x1 = (3 + √53)/2
x2 = (3 - √53)/2
-
Perguntas interessantes
Química,
11 meses atrás
Matemática,
11 meses atrás
Ed. Física,
11 meses atrás
Física,
1 ano atrás
Português,
1 ano atrás